Clinical outcomes during and after wearable cardioverter defibrillator use in Japanese patients with heart failure: A single‐center experience - Noriko Kikuchi; Tsuyoshi Shiga; Yohei Sugawara; Atsushi Suzuki; Yoshiaki Minami; Hidetoshi Hattori; Morio Shoda; Nobuhisa Hagiwara; Junichi Yamaguchi (Journal of Arrhythmia)
Abstract Background A wearable cardioverter defibrillator (WCD) is indicated for a limited period in patients at high risk of sudden cardiac death (SCD). Nonischemic heart failure (HF) is common among Japanese patients with HF. The aim of this study was to evaluate the incidence of fatal arrhythmias during WCD use and the clinical outcomes after WCD withdrawal in Japanese patients with HF. Methods We retrospectively studied 105 hospitalized HF patients who were discharged with a WCD. The main outcome was SCD/ventricular arrhythmias during WCD use and the other outcomes were implantation of an implantable cardioverter‐defibrillator (ICD), SCD/ventricular arrhythmias after WCD withdrawal, and changes in left ventricular ejection fraction (LVEF). Results Eighty‐seven (83%) patients received a WCD for primary prevention of SCD, of whom 60 (69%) were new‐onset HF patients with an LVEF ≤35%. The median daily wear time was 22.1 h. Two patients experienced sustained ventricular tachycardia and one patient experienced atrioventricular block with asystole while on WCD. After WCD withdrawal, 81 (77%) patients decided not to receive ICD implantation. The percentage of patients with an LVEF ≥35% increased from 20% at baseline to 70% at 1 year after discharge. During the median follow‐up of 50 months, 78 (96%) of the 81 patients who did not have an ICD were free of SCD/ventricular arrhythmias. Conclusions The use of a WCD is useful for determining the appropriate indication for ICD implantation in Japanese patients with new‐onset HF, a low LVEF, and a risk of SCD.